2021
DOI: 10.1134/s1070428021110105
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Activity of Substituted 2-[2-(Diphenylmethylene)hydrazinyl]-5,5-dimethyl-4-oxohex-2-enoates

Abstract: The synthesis of new substituted 2-[2-(diphenylmethylene)hydrazinyl]-5,5-dimethyl-4-oxohex-2-enoates is described. The synthesis from commercially available starting materials included the preparation of 5,5-dimethyl-2,4-dioxohexanoic acid via Claisen condensation of 3,3-dimethylbutan-2-one (pinacolone) and diethyl oxalate in the presence of sodium methanolate. The resulting acid reacted with (diphenylmethylene)hydrazine to form 2-[(diphenylmethylene)hydrazono]-5,5-dimethyl-4-oxohexanoic acid. The initial 5-(t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Such a universal structural fragment can be found among the 3-imino-(hydrazinylidene)-furan-2(3H)-one derivatives, which results from their chemical availability due to the scalability of the synthetic methods [8] and the reactivity [9][10][11][12][13][14][15]. For example, the reactions of 3-imino-(hydrazinylidene)-furan-2(3H)-ones derivatives with various nucleophilic reagents lead to the attack on the carbonyl group of the lactone fragment and to the for-mation of acyclic or heterocyclic structures [16][17][18][19][20][21] that retain the pharmacophore fragment of 2,4-dioxobutanoic acid [22][23][24][25][26][27][28][29][30][31][32]. This fragment was found in the structure of various biologically active and natural compounds [33,34], which indicates that this idea is worth developing.…”
Section: Introductionmentioning
confidence: 99%
“…Such a universal structural fragment can be found among the 3-imino-(hydrazinylidene)-furan-2(3H)-one derivatives, which results from their chemical availability due to the scalability of the synthetic methods [8] and the reactivity [9][10][11][12][13][14][15]. For example, the reactions of 3-imino-(hydrazinylidene)-furan-2(3H)-ones derivatives with various nucleophilic reagents lead to the attack on the carbonyl group of the lactone fragment and to the for-mation of acyclic or heterocyclic structures [16][17][18][19][20][21] that retain the pharmacophore fragment of 2,4-dioxobutanoic acid [22][23][24][25][26][27][28][29][30][31][32]. This fragment was found in the structure of various biologically active and natural compounds [33,34], which indicates that this idea is worth developing.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that 2-(2-(4-R-benzoyl)hydrazono)-4-oxobutanoic and 2-(thiophen-2-ylamino)-4-oxobut-2-enoic acids and their derivativities exhibit analgesic [31,32], anti-inflammatory [16] antimicrobial activity [24] and photoluminescent properties [33,34]. We continue to search for new biologically active compounds with low toxicity [35] and expand the methods for the synthesis of 2,4-dioxobutanoic acid and 3-hydrazonofuran-2(3H)-one derivatives. In this paper, synthesis and anti-inflammatory activity of new 2,4-dioxobutanoic acids derivatives are discussed.…”
Section: Introductionmentioning
confidence: 99%